EVALUASI TRANSAKSI MUDHARABAH BERBASIS PENDAPAT ULAMA SYAFI'YAH: KASUS PADA BANK SYARIAH X - Wahyu Dewi Hapsari; Slamet Sugiri Sodikin (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2017)
Bank Sharia X, located in certain city in the province of central Java, is one of branches of Bank Muamalat Indonesia. As the name implies, Bank Sharia X operates its business based on Islamic rules (Al-Qur’an and Al-Hadist). In interpreting the Al-Qur’an and Al-Hadist, Islamic scholars have different opinions on requirements of some specific topics, such as those on mudharaba transaction. Among the great schools of thoughts are Syafi’iya, Malikiya, Hanafiya, and Hanabila. We aim to identify whether or not Bank Sharia Xfully applies its mudharaba transaction based on Syafi’iya’sschool of thought. We collect data by interviewing key persons of the bank and investigating important, corroborating documents out there. We analyze the data by comparing between the application of mudharaba transaction and the Shafee’s school of thought on the themudharaba transaction. Based on our analysis, we find that Bank Sharia X applies its mudharabatransaction based on the requirements of Shafee’s thought except on (a) ijab and qabul, and (b) time limitation.